Making a Difference: Knowledge Activism and Worker Representation in Joint OHS Committees - Hall, Alan; Forrest, Anne; Sears, Alan; Carlan, Niki (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2006)
This article elaborates the concept of knowledge activism as a way of understanding effective health and safety representation within the current Ontario legal regime of internal responsibility. Based on interviews with unionized health and safety representatives in the auto industry, we suggest that knowledge activism is a form of political activism by worker health and safety representatives that is organized around the strategic collection and tactical use of technical, scientific and legal knowledge. We argue that knowledge activism is more effective with reference to larger scale changes in work processes, workplace organization and technologies, and with reference to occupational health issues. Knowledge activism is conceptualized as an effective adaptation to a legislative regime which involves worker representatives in decisions without providing substantive power or proactive enforcement support.